Drug Delivery: A Dual‐Bioresponsive Drug‐Delivery Depot for Combination of Epigenetic Modulation and Immune Checkpoint Blockade (Adv. Mater. 17/2019). Issue 17 (18th April 2019) - Ruan, Huitong; Hu, Quanyin; Wen, Di; Chen, Qian; Chen, Guojun; Lu, Yifei; Wang, Jinqiang; Cheng, Hao; Lu, Weiyue; Gu, Zhen
Abstract : In article number1806957, Weiyue Lu, Zhen Gu, and co‐workers engineer a dual bioresponsive drug‐delivery depot that can respond to the acidic pH and reactive oxygen species within the tumor microenvironment for co‐delivery of anti‐PD1 antibody and an epigenetic modulator. This combination therapy increases the immunogenicity of cancer cells and enhances the antitumor immune response. The pond represents the drug‐delivery depot, the duckweeds represent the tumor cells; the red fish (epigenetic agent) and the black fish (aPD1 antibody) work together to eat the duckweeds, representing the tumor cells being eliminated.